Electroconvulsive therapy, personal protective equipment and aerosol generating procedures: a review to guide practice during Coronavirus Disease 2019 (COVID-19) pandemic. (December 2020) - Purushothaman, Subramanian; Fung, David; Reinders, Jonathan; Garrett-Walcott, Simone; Buda, Margaret; Moudgil, Vikas; Emmerson, Brett
Objective: To review the literature on the definition of aerosol-generating procedures (AGPs), identify high-risk AGPs, guidelines to use personal protective equipment (PPE) and review evidence to see if electroconvulsive therapy (ECT) is a high-risk AGP requiring the use of PPE. Methods: Existing guidelines and research data were reviewed to answer the questions. Results: There is consensus about the type of anaesthesia used during ECT, what constitutes AGPs and what PPE should be used. It was not clear if ECT was an AGP, but we argue that it is one based on evidence. Conclusion: We conclude that ECT is an AGP and that it requires the appropriate use of PPE after taking in to account local supply and demand.